A multi-dimensional genre analysis of tourism homepages and web-mediated advertorials / Cecilia Cheong Yin Mei - Cecilia Cheong , Yin Mei (2013)
The tourism industry, which is now a global enterprise promoting tourist destinations in both domestic and international markets, has captured the relevance of the Internet as a new mass medium in attracting potential tourists from all over the world. In order to promote a country as a holiday destination to foreigners as well as locals, governments and advertisers have now resorted to creating websites in an attempt to advertise their countries, places of interest and attractions via the Internet. The present study is a multidimensional investigation of the web-mediated promotional genre of tourism advertorials from a two-pronged analytical approach of genre analysis and multimodal discourse analysis. It investigates how tourism homepages and web-mediated tourism advertorials are composed to attract potential tourists to visit the country and its places of interest through the web genres in which the persuasive and communicative features are used together with multimodal features. This is achieved by examining the organisational patterns of sixteen official Malaysian tourism homepages from the macro-genre level based on Marco’s (2002) analytical model for corporate homepages, and forty-nine advertorials from the micro-genre level based on a combination of Kathpalia’s (1992) and Bhatia’s (1993 & 2004) analytical models for promotional texts. The study also investigates how multimodal features are used in the tourism homepages and online advertorials to serve the informative and persuasive communicative purposes based on Kress and van Leeuwen’s (1996, 2006) multimodal discourse analysis framework. In order to obtain a more comprehensive contextual view and to provide a thicker description of the cyber genre, this study also investigates the online tourism genre from a multi-perspective viewpoint which goes beyond the textual data to include the investigation of a number of socio-pragmatic aspects of construction (socio-critical perspective), use (ethnographic perspective) and interpretation (socio-cognitive perspective) of the discourse as proposed by Bhatia (2004). These were accomplished via interviews with specialist informants, and disseminating a questionnaire to tourists. Web-mediated advertorials are considered an effective tool of mass communication where they can reach a huge target audience. Therefore, it is vital that such texts need to be produced and communicated effectively in order to be successfully promotional, and also to convey a positive image of the tourism products and services as well as its provider or advertiser. The analyses of the web genre and findings have shown that there are certain obligatory rhetorical structures that are pertinent in Malaysian online tourism advertorials. This contributes to a better understanding to the web-mediated genre. The specialist informants interviewed in the study have also shed light on how such online promotional materials are produced. Their views and findings from the tourists’ questionnaire have been incorporated in developing a guideline for producing effective promotional materials, specifically online tourism advertorials that can achieve the objectives of promoting, advertising and marketing or selling a product, brand or service via the Internet. This study enhances knowledge specifically in the areas of genre analysis and multimodality, and online communication in general, as these areas are continually evolving in this era of globalisation.